2019
DOI: 10.1371/journal.pone.0215620
|View full text |Cite
|
Sign up to set email alerts
|

HIV disease, metabolic dysfunction and atherosclerosis: A three year prospective study

Abstract: HIV infection is known to be associated with cardiometabolic abnormalities; here we investigated the progression and causes of these abnormalities. Three groups of participants were recruited: HIV-negative subjects and two groups of treatment-naïve HIV-positive subjects, one group initiating antiretroviral treatment, the other remaining untreated. Intima-media thickness (cIMT) increased in HIV-positive untreated group compared to HIV-negative group, but treatment mitigated the difference. We found no increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Finally, we compared exosomes isolated from plasma of uninfected volunteers and from HIV-infected subjects. Plasma was pooled from 4 uninfected and from 4 HIV-infected subjects undergoing treatment with ART and described in our recent study [19]. Exosomes from HIV-infected, ART treated donors (HIV+) reduced cholesterol efflux as well as abundance of total and cell-surface ABCA1 compared to exosomes from uninfected individuals (Fig 2I and 2J).…”
Section: Resultsmentioning
confidence: 97%
“…Finally, we compared exosomes isolated from plasma of uninfected volunteers and from HIV-infected subjects. Plasma was pooled from 4 uninfected and from 4 HIV-infected subjects undergoing treatment with ART and described in our recent study [19]. Exosomes from HIV-infected, ART treated donors (HIV+) reduced cholesterol efflux as well as abundance of total and cell-surface ABCA1 compared to exosomes from uninfected individuals (Fig 2I and 2J).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, recent studies have shown that Nef can be released from infected cells through extracellular vesicles altering cholesterol metabolism in uninfected recipient cells [237,[243][244][245]. It is well known that HIV patients develop dyslipidemia, and their HDL-C plasma concentrations can be as low as those of TD patients [60,246,247]. The Nef protein causes dyslipidemia, as it affects cholesterol efflux by reducing the expression of ABCA1 in in vitro and in vivo models [237,[248][249][250].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…The aims of this study were to investigate the effect of HIV infection and c-ART on LDL particle phenotype and atherogenesis-related biomarkers in a cohort of treatment-naïve HIV-infected patients and to assess the relationship between these variables and subclinical carotid atherosclerosis. The data we report can be added to findings published recently by our group on other atherogenesis-related pathways, mainly metabolism of HDL [ 26 ]. To our knowledge, no previous studies have compared biomarkers of cardiovascular disease in treatment-naïve HIV-infected patients starting or not starting c-ART and a healthy control group.…”
Section: Introductionmentioning
confidence: 60%